Openness and visibility - Rudgard, Stephen (Technical Centre for Agricultural and Rural Cooperation, 2013)
This issue's guest editor, Stephen Rudgard from FAO, is a major actor in opening agricultural knowledge online. He has asked a number of experts from different backgrounds to provide their perspective on various aspects of opening access to content